Can anaerobic digestion of sugar beet pulp support the circular economy? a study of biogas and nutrient potential. (March 2018) - Suhartini, S; Heaven, S; Banks, C J
Abstract: Anaerobic digestion (AD), known as a biological process without oxygen to convert complex organic materials into biogas, is capable of processing large tonnage quantities of biomass, such as sugar beet pulp (SBP). In addition to biogas production, its use allows nutrients and organic carbon recycle back to agriculture through the spreading of digestate. Digestate still contains high amount of nutrients (N, P, K) for use as biofertiliser. The aims of this research were to determine biogas/methane potential as a baseline for comparison with performance in semi-continuous digestion, and to determine nutrient and potentially toxic elements (PTE) of digestate fractions with respect to their potential for utilisation in agriculture. The Biochemical Methane Potential (BMP) test was performed in triplicate against blank and positive controls over a period of 28 days with gas measured at regular intervals. Semi-continuous AD of SBP was operated under mesophilic and thermophilic condition for 206 and 165 days. The results indicated that SBP is a very promising feedstock for AD, with the average BMP of 0.321 l CH4 g-1 VS and biogas potential of 0.605 l g-1 VS. Under semi-continuous operation, SBP also demonstrated positive results. Digestates from mesophilic and thermophilic AD of SBP contained useful quantities of N, P and K, with an acceptable Ni concentration in accordance to limits for PTE. These results suggest that digestate has the potential to be utilised on agricultural and arable land. This study illustrated the positive effects of applying AD to the achievement of economic savings and environmental-friendly performance.